2022
DOI: 10.3390/su14095176
|View full text |Cite
|
Sign up to set email alerts
|

Classifications of Sustainable Factors in Blockchain Adoption: A Literature Review and Bibliometric Analysis

Abstract: Blockchain is a cutting-edge technology that is transforming and reshaping many industries. Hence, the adoption of Blockchain is becoming an increasingly significant topic. The number of publications discussing the potential of Blockchain adoption has been expanding significantly. In addition, not enough attention has been given to Blockchain adoption in the software development industry. As a result, a systematic overview to investigate the research trends in this area is needed. This study uses a Scientometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…In addition, (Dadhich & Hiran, 2022) also reported that economic, social, technological, and organizational factors were positively related to organizational performance via the environmental sustainability of firms (Chege & Wang, 2020;Alraja et al, 2022;Aboelmaged, 2018;Hanna et al, 2021;Shee et al, 2021;Yavuz et al, 2023;Karmaker et al, 2022;Contini et al, 2023). (Al-Ashmori et al, 2022) show that there are different models that explain the acceptance and implementation of innovative applications, such as the Technology Readiness Index, the Planned Behavior Theory, the Task Fit Technology Model, the Unified Technology Acceptance and Use Theory, the Technology Acceptance Model. Indeed, (Verma et al, 2022) show that the technological dimension coincides with the results of industrial revolutions in terms of operational practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, (Dadhich & Hiran, 2022) also reported that economic, social, technological, and organizational factors were positively related to organizational performance via the environmental sustainability of firms (Chege & Wang, 2020;Alraja et al, 2022;Aboelmaged, 2018;Hanna et al, 2021;Shee et al, 2021;Yavuz et al, 2023;Karmaker et al, 2022;Contini et al, 2023). (Al-Ashmori et al, 2022) show that there are different models that explain the acceptance and implementation of innovative applications, such as the Technology Readiness Index, the Planned Behavior Theory, the Task Fit Technology Model, the Unified Technology Acceptance and Use Theory, the Technology Acceptance Model. Indeed, (Verma et al, 2022) show that the technological dimension coincides with the results of industrial revolutions in terms of operational practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bibliometric study of the blockchain technology field has increased tremendously, particularly in terms of the number of blockchain-related research articles [34]. These research works discuss the growth, trends, and impacts of new developments in blockchain science, including the number of blockchain-related research articles, patents, and citations.…”
Section: Bibliometric Work In Blockchainmentioning
confidence: 99%
“…The bibliometric software helps to accurately classify and review a vast amount of information captured in studies over a specified time period. Unlike the systematic literature reviews, which often apply qualitative methodologies and are susceptible to interpretation biases due to researchers' diverse academic and disciplinary backgrounds, systematic reviews and bibliometric analyses apply statistical methods to research and thus are not at risk of bias [34]. On the other hand, datasets of the articles used in bibliometric analyses can be exported from multiple databases, such as Web of Science (WoS), Scopus, PubMed, and Google Scholar.…”
Section: Data Collectionmentioning
confidence: 99%
“…This technology facilitates the flow of essential data while keeping it private and secret. It is an ideal solution for securely storing all linked papers in one area [ 173 , 174 , 175 ]. Using a single patient database, Blockchain also speeds up searches for candidates who meet certain trial requirements.…”
Section: Blockchainmentioning
confidence: 99%